Implementasi Model Waterfall Untuk Pengembangan Sistem Informasi Surat Berjalan PKK DKI Jakarta - Andi Nana Mariana; Amrin Amrin (JURIKOM (Jurnal Riset Komputer), 2019)
PKK (Family Welfare Education) of DKI Jakarta Province is an institution that houses all PKK in the DKI Jakarta area. Currently, PKK of DKI Province often experiences difficulties in the approval of activity letters, the activity letters submitted at the Jakarta Provincial PKK are still manual and the busy schedule of the DKI Jakarta PKK chairman. This caused frequent disruption of activity schedules, so the author designed a running mail system where the PKK chairman could approve PKK activities without having to be in place. The scope of this application is limited from input data of the letter request for activities from the Working Group to the input letter of approval issued by the chairman of PKK. This application is designed using waterfall method. Besides that the author also makes system design using UML, using PHP programming language, codeigniter framework, and MySQL as the database. With the design of this running mail system, it is expected that activities in the PKK can run well.